(untitled) (Journal of the College of Basic Education, 2023)
Abstract This study intends to shed some light on why Iraq has been in the news quite a bit, and why it has come to play the role it has in world affairs of the late twentieth and early twenty-first centuries. It concerns Iraq yesterday and today. Introduction The paper makes one simple assumption: the notion that all human life on this planet – Muslim and non-Muslim, female and male, civilian and military, poor or rich, ‘North’ or ‘South’, white or black– carries exactly the same intrinsic worth. This essential value of human life is due to the presence of the Divine spirit in all of humanity, the same spirit that, according to the Qur’an, God breathed into each and every human being [Qur’an 15:29 and 38:72]. From this premise of the worth and dignity of each and every human life and the right of each community to realize their vision of prosperity, dignity and righteousness, as long as that vision does not come at the expense of any other community, the researcher intends to begin this study. The paper is divided into two parts, the first concerns Iraq before the war of 2003 – referred to in this study as Iraq yesterday; the second part tackles a number of current issues and attempts to find answers for some controversial questions including: What are the causes and consequences of the US war on Iraq and the occupation of this country? Is it invasion or liberation? Is it true that post-war excuses for invasion and occupation are to make Iraq a western-style democracy and to spread Western values or is the US actually putting on a terrifying show for the whole world to see and yield? And eventually where is the value of human life?